On the Relationship between Cognitive and Sensory Phenomenology - Elisabetta Sacchi (Rosenberg & Sellier, 2017)
My main aim in this paper is to consider what methodology is best suited to adopt for one who believes that there is cognitive phenomenology (CP) in order to argue for its irreducibility to sensory phenomenology. I shall first present and criticize a methodology widely adopted by the deniers of CP in order to reject the irreducibility claim, the so called “exclude-and-isolate” methodology. I shall use my criticisms against it as a lever for backing up a certain conception of the nature of cognitive phenomenal properties. The key notion in this conception is that of factual intimacy which I shall mobilize to put forward the idea that cognitive phenomenal properties are inseparable, in practice and in ordinary cases, from sensory phenomenal properties (leaving open the possibility of their explanatory and metaphysical independence). I shall then present a strategy to prove irreducibility which is compliant with the inseparability claim. One such strategy is in my view provided by combining the so-called phenomenal contrast methodology with a methodology that, instead of contrasting couples of cases, compares them in order to disclose the presence of phenomenological commonalities. What the comparison methodology shows is that experiences with different sensory features can share a common phenomenal component. Since this possibility obtains even by assuming that all of a subject’s sensory features differ, it follows that the common phenomenal component cannot be sensory in nature. This is enough to prove that the phenomenology in question is cognitive and that this phenomenology is irreducible to the sensory one.